Fabrication and properties of in-situ pressureless-sintered ZrB2/B4C composites. Issue 17 (1st December 2017) - Lin, Xiao; Ai, Shuhe; Feng, Yurun; Gao, Dezhi; Guo, Xue; Liu, Yu; Xie, Bingying; Gong, Hongyu; Zhang, Yujun
Abstract: The effect of ZrO2 addition on the mechanical properties of B4 C ceramics prepared by pressureless sintering was investigated. Submicron B4 C powders, phenolic resin as binders and submicro-sized ZrO2 as sintering aids were used. Results show that the addition of ZrO2 improves the relative density and mechanical properties of B4 C remarkably. The highest relative density was 96.7%, meanwhile bending strength and Vickers hardness of 365.4 MPa and 34.2 GPa, respectively were measured for specimens added with 15 wt% ZrO2 and pressureless sintered at 2100 °C for 60 min.